Penggunaan media pembelajaran dengan menggunakan SlideGo dan model pembelajaran example non-example untuk meningkatkan hasil belajar siswa pada materi sistem ekskresi - Pertiwi, Wiwin (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
Lack of facilities and infrastructure, and lack of accuracy in the selection of media and learning methods cause students to experience difficulty in receiving lessons from field teachers, this is indicated by the results of working on test sheets using the lecture method, from 36 students who have scored 80, only 6 people, while 30 other students still have not reached the minimum completeness criteria. So learning is implemented using SlidesGo Â media and Example and Non-Example learning models. This study aims to determine students' cognitive science learning outcomes using SlidesGo Â media and Example and Non-Example learning models. This research method is Classroom Action Research (PTK) carried out in two cycles, each cycle consisting of two meetings consisting of planning, action, observation, and reflection stages. The research subjects were 36 students of class VIII G even semester of the 2019/2020 academic year. Data collection tools used observation sheets and tests. Data analysis using descriptive analysis techniques. Data from the results of observations and tests in each cycle become the basis or material for improvement in the next cycle. The application of learning using SlidesGo Â media and the Example and Non-Example learning model, proved to be very effective in improving student learning outcomes, it can be seen from 36 students, in cycle I got an average of 75.43 and in cycle II got an average of 86 , 69. The value obtained has increased by 11.26 points. The results showed that there was an increase in student cognitive learning outcomes in each cycle after the use of application media and the Example Non-Example learning model on excretory material.